Body Adiposity Index, but not Visceral Adiposity Index, Correlates with Inflammatory Markers in Sarcopenic Obese Elderly Women. Issue 3 (27th May 2017) - Dutra, Maurílio Tiradentes; Gadelha, André Bonadias; Nóbrega, Otávio Toledo; Lima, Ricardo Moreno
Abstract : Background/Study Context: The association of body adiposity index (BAI) and visceral adiposity index (VAI) with inflammatory markers has yet to be understood. The aim of this work was to investigate the association of BAI and VAI with inflammatory markers in elderly women with sarcopenic obesity (SO). Methods: A total of 130 women (age: 66.7 ± 5.2 years) underwent body composition analysis by dual-energy x-ray absorptiometry (DEXA). Volunteers were classified according to SO definition. BAI, VAI, and waist-to-hip ratio (WHR) were calculated. Blood samples were collected for C-reactive protein (CRP), tumor necrosis factor, and interleukin-6 (IL-6) measurements. Results: SO prevalence was 20.8%. BAI correlated with the DEXA-derived body fat content ( r S  = .90), CRP ( r S  = .55), and IL-6 ( r S  = .53), whereas WHR correlated with CRP ( r S  = .60) only (all p  < .01). VAI did not correlate with any of the inflammatory variables. Conclusion: Simple and cheap anthropometric indices such as BAI and WHR may be better predictors of low-grade inflammation than VAI in elderly women with SO.